2004
DOI: 10.1161/01.atv.0000120374.59826.1b
|View full text |Cite
|
Sign up to set email alerts
|

Brain Cholesterol: Long Secret Life Behind a Barrier

Abstract: Abstract-Although an immense knowledge has accumulated concerning regulation of cholesterol homeostasis in the body, this does not include the brain, where details are just emerging. Approximately 25% of the total amount of the cholesterol present in humans is localized to this organ, most of it present in myelin. Almost all brain cholesterol is a product of local synthesis, with the blood-brain barrier efficiently protecting it from exchange with lipoprotein cholesterol in the circulation. Thus, there is a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
756
1
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 894 publications
(776 citation statements)
references
References 112 publications
13
756
1
6
Order By: Relevance
“…A recent report has also shown that feeding cholesterol to young, normal rats improves learning in the Morris water maze (Dufour, Liu, Gusev, Alkon, & Atzori, 2006). Given that dietary cholesterol does not cross the blood brain barrier in any appreciable amount (Bjorkhem & Meaney, 2004;Dietschy & Turley, 2001;Dietschy & Turley, 2004;Tuma & Hubbard, 2003), it remains to be determined how heart rate conditioning, which is controlled in part by the amygdala via the dorsal motor nucleus of the vagus, was increased as a result of a cholesterol-rich diet. The same would be true for the effects of cholesterol on rat water maze learning (Dufour et al, 2006) and previous research showing that addition of cholesterol to the diet of animals deficient in cholesterol or animals that have cholesterol synthesis blocked reverses learning and memory deficits (Endo, Nishimura, & Kimura, 1996;O'Brien et al, 2002;Voikar, Rauvala, & Ikonen, 2002;Xu et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has also shown that feeding cholesterol to young, normal rats improves learning in the Morris water maze (Dufour, Liu, Gusev, Alkon, & Atzori, 2006). Given that dietary cholesterol does not cross the blood brain barrier in any appreciable amount (Bjorkhem & Meaney, 2004;Dietschy & Turley, 2001;Dietschy & Turley, 2004;Tuma & Hubbard, 2003), it remains to be determined how heart rate conditioning, which is controlled in part by the amygdala via the dorsal motor nucleus of the vagus, was increased as a result of a cholesterol-rich diet. The same would be true for the effects of cholesterol on rat water maze learning (Dufour et al, 2006) and previous research showing that addition of cholesterol to the diet of animals deficient in cholesterol or animals that have cholesterol synthesis blocked reverses learning and memory deficits (Endo, Nishimura, & Kimura, 1996;O'Brien et al, 2002;Voikar, Rauvala, & Ikonen, 2002;Xu et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Adding to this unique lipid environment is the synthesis of cholesterol within the brain, predominantly in glial cells, without significant import from the liver 3. Neuronal cholesterol is dysregulated in AD, and persistent neuronal damage response may increase cholesterol biosynthesis 4.…”
Section: Introductionmentioning
confidence: 99%
“…The early expression of Xdhcr7 is in accordance with the multiple developmental defects reported in DHCR7 mutations (Porter, 2000;Waterham and Wanders, 2000;Nowaczyk and Waye, 2001;WitschBaumgartner et al, 2001;Ciara et al, 2004), since the reported phenotypes may result from a failure of early patterning events. Accumulating data support the idea that the human brain depends for the most part on de novo synthesised cholesterol, owing to the selectivity of the blood-brain barrier (Muenke and Cohen, 2000;Turley, 2001, 2004;Woollett, 2001;Herz and Bock, 2002;Pfrieger, 2003b;Waage-Baudet et al, 2003;Bjorkhem and Meaney, 2004). In tadpoles, Xdhcr7 expression is prominent in brain structures (Fig.…”
Section: The Expression Of Xdhcr7 Is Spatially Restricted and Overlamentioning
confidence: 83%